2023
DOI: 10.1371/journal.pone.0281717
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils prolonged the cut carnation longevity by limiting the xylem blockage and enhancing the physiological and biochemical levels

Abstract: Postharvest characteristics, such as vase life and antimicrobial preservation of commercial cut flowers are some of the major determinants of their market value worldwide. Extending vase life while restricting microbial proliferation in cut flowers is an important challenge faced by floricultural researchers. This study evaluates the preservative efficiency of different essential oils used as additive solutions in prolonging the longevity of carnation cv. Madam Collette cut flowers and restricting microbial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The implications of these results are particularly relevant in understanding the decay mechanisms in cut flowers. As identified by Gururani et al [ 16 ], one of the primary causes of decay in cut flowers is the blockage of stem vessels due to microbial contamination or chemical residues, which impedes the stem's ability to absorb water. The presence of such microbial contamination in preservative solutions is a critical factor in the deterioration of cut flowers.…”
Section: Resultsmentioning
confidence: 99%
“…The implications of these results are particularly relevant in understanding the decay mechanisms in cut flowers. As identified by Gururani et al [ 16 ], one of the primary causes of decay in cut flowers is the blockage of stem vessels due to microbial contamination or chemical residues, which impedes the stem's ability to absorb water. The presence of such microbial contamination in preservative solutions is a critical factor in the deterioration of cut flowers.…”
Section: Resultsmentioning
confidence: 99%
“…By maintaining the water balance, the ornamental appeal and longevity of cut flowers can be significantly improved, thereby enhancing both their commercial value and consumer satisfaction (Li et al, 2021). Water loss reduction and water balance maintenance provide energy from carbohydrate metabolism to the petal cells (Gururani et al, 2023). It has been shown that a combined treatment with nano silver and aminoethoxyvinylglycine prevents water stress, which helps to maintain cell turgor and improve flower opening (Ha and In, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The initial screening in this work showed ginger and citronella essential oils to have only a slight effect on the vase life of Dendrobium orchids, while peppermint essential oil notably extended vase life. It has been indicated that the efficacy of plant essential oils is dependent on their phytochemical composition and concentration [ 36 ] and, more specifically, on antimicrobial and antioxidant activities that reflect the composition and concentration of the oil's bioactive constituents [ 14 , 37 ]. The vase life of cut orchids in solutions containing 4 % glucose in combination with peppermint essential oil was 6–7 days longer than that of control flowers in distilled water ( Fig.…”
Section: Discussionmentioning
confidence: 99%